Incidence of injury and illness during the 2013 world dwarf games - Mathew R. Saffarian; Jensen J. Swampillai; Michael T. Andary; Jim R. Sylvain; Salina E. Halliday; Brian Bratta (BMC, 2019)
Abstract Background Dwarfism, or skeletal dysplasia, is a term used to describe short stature. Injuries to athletes with disabilities and medical co-morbidities, such as those present in the dwarf population, can have significant consequences on functionality. The main objectives of this retrospective descriptive study were to 1) evaluate the safety of athletic participation among athletes with skeletal dysplasia, 2) investigate the incidence and characteristics of injuries and illnesses among athletes with skeletal dysplasia during the 2013 World Dwarf Games held on the campus of Michigan State University, 3) describe details and overview of the World Dwarf Games, and 4) identify possible safety and rule issues to improve safety at future World Dwarf Games. Methods This was a retrospective review of case series interactions between dwarf athletes and the medical staff present at the 2013 World Dwarf games from August 3-10, 2013. Injury incidence rates were calculated by dividing the number of incident injuries by total athlete-competitions. Epidemiologic incidence proportion calculations were used to measure average injury risks. Results A total of 24 competition related injuries were recorded among the 409 athletes. Only 1 illness (otitis media) was reported during the week of games. The overall injury incidence rate was found to be 0.78 injuries per 100 athlete-competitions. The overall epidemiologic incidence proportion was 5.9% (7.2% for males, 3.0% for females). The most common type of injury was a muscle/tendon strain (41.7% of all injuries). The sport with the most reported injuries was soccer with 4.63 injuries per 100 athlete-competitions. Conclusions Based on the data collected, it does appear that athletes with skeletal dysplasia can safely participate in the events offered during the World Dwarf Games. None of the reported injuries or illnesses precluded the athletes from returning to play. Data collected at future competitions will help identify trends, which may lead to rule changes to improve safety and a decrease in injuries. Adding a designated spectator area for athletes as well as modifying rules to prevent excessive physical contact in soccer and basketball competitions may reduce the incidence of injury.